Adaptive control design and implementation for collective pitch in wind energy conversion systems. (July 2020) - Lasheen, Ahmed; Elnaggar, Mahmoud; Yassin, Haitham
Abstract: This paper introduces a discrete-time L 1 adaptive controller design for collective pitch control for variable speed variable pitch wind turbines. In this control algorithm, the blades' pitch angles are regulated to manipulate the generator speed and generated power during high speeds wind airflow. The main merits of the proposed controller are its robustness against the wind turbine model uncertainties, guaranteeing the closed loop system stability and performance, and applicability during implementation in real life. Commonly used industrial gain-scheduled PI controller is used to be compared with the proposed controller. The proposed scheme is simulated using a 5-MW offshore turbine model and the obtained results illustrates the superior performance of the proposed controller. Further, a reduced scale wind turbine emulator is used to provide hardware in the loop to test the implementation of the proposed controller. The controller is implemented using laboratory equipment to demonstrate the feasibility of the controller for real time applications. The obtained experimental results validate the closed loop system performance enhancement due to replacing the traditional PI controller with the proposed design. Highlights: A proposed discrete adaptive controller for CPC is analyzed. The pitch constraints are taken into consideration in the proposed controller. For a chosen sampling interval, the proposed design ensures stability and robustness. Simulation and experimental results of the controller are presented and discussed.